Neutrophil autophagy induced by monosodium urate crystals facilitates neutrophil extracellular traps formation and inflammation remission in gouty arthritis - Huang, Shanshan; Wang, Yaohui; Lin, Shibo; Guan, Wei; Liang, Hui; Shen, Jiajia (Frontiers in Endocrinology, 2023)
Neutrophil extracellular traps (NETs) are composed of chromatin filaments coated with granular and cytosolic proteins, which contribute to the pathogenesis and progression of immune-related diseases. NETs are frequently observed in gouty arthritis, but the related mechanisms remain poorly understood. The aim of our study was to systematically elucidate the molecular mechanisms of self-remitting effects in gouty arthritis, and the causative relationship between neutrophil autophagy and NETs. The air pouch and paw edema model were used to simulate gouty arthritis in mice. Neutrophil infiltration and the formation of NETs were found in gouty arthritis. Interestingly, monosodium urate (MSU) crystals could induce the formation of NETs, degrade inflammatory factors, and alleviate the inflammatory response in gouty arthritis. In addition, MSU crystals resulted in profound molecular alterations in neutrophils using RNA-seq analysis, including autophagy activation. MSU crystals could activate neutrophil autophagy in vitro, and autophagy activators and inhibitors could regulate the formation of NETs. Furthermore, we explored the mechanism of autophagy-induced NETs. Autophagy related protein 7 (ATG7) produced by neutrophils stimulated with MSU crystals worked synergistically with p53 to enter the nucleus, promoting peptidyl arginine deiminase 4 (PAD4) expression, and inducing the formation of NETs. Finally, we substantiated that neutrophil autophagy regulates the severity of gouty arthritis via the formation of NETs in PAD4 -/- mice. Our results indicated that the autophagy of neutrophils regulates the formation of NETs and degrades inflammatory factors. Regulating autophagy and interfering with the formation of NETs represents a potential therapeutic approach against gouty arthritis during clinical practice.